2023
DOI: 10.3389/fmed.2023.1169970
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognostic factors for PRRT in neuroendocrine tumors

Abstract: Aim/introductionPeptide receptor radionuclide therapy (PRRT) is an effective and well-tolerated treatment option for patients with neuroendocrine tumors (NETs) that prolongs progression-free survival (PFS). However, the limited overall survival (OS) rates in the prospective phase III study (NETTER1) highlighted the need to identify patient-specific long-term prognostic markers to avoid unnecessary side effects and enable better treatment stratification. Therefore, we retrospectively analyzed prognostic risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Furthermore, precise tumor burden quantification might be a valuable tool for assessing an individual's risk and prospective prognosis. Studies have shown that parameters such as metabolic tumor volume (MTV), an imaging-derived metric, serve as predictors for outcomes in various types of cancer treated with RNT [34][35][36]. While manual evaluations of tumor burden offer crucial insights, they are labor-intensive, which hampers the routine use of volumetric parameters like MTV in clinical practice.…”
Section: Patient Selection and Risk Stratificationmentioning
confidence: 99%
“…Furthermore, precise tumor burden quantification might be a valuable tool for assessing an individual's risk and prospective prognosis. Studies have shown that parameters such as metabolic tumor volume (MTV), an imaging-derived metric, serve as predictors for outcomes in various types of cancer treated with RNT [34][35][36]. While manual evaluations of tumor burden offer crucial insights, they are labor-intensive, which hampers the routine use of volumetric parameters like MTV in clinical practice.…”
Section: Patient Selection and Risk Stratificationmentioning
confidence: 99%